EFFECT OF CHEMICAL TREATMENTS ON QUALITY AND VASE LIFE OF CUT CARNATION (DIANTHUS CARYOPHYLLUS L.) CVS. MASTER AND YELLOW CANDY - S. SUGANYA,; M. KALAIMANI,; J. PADMANABAN, (The Bioscan, 2020)
An experiment was undertaken during 2016-2017 at the laboratory of Department of Horticulture, Annamalai University, to study the effect of different chemicals on quality and vase life of cut carnation flowers Cvs. Master and Yellow Candy. The selected flowers were analysed using Completely Randomized Design and held in different holding solutions containing STS (0.5 mM, 1.0 mM and 1.5 mM), salicylic acid, silver nitrate, boric acid, citric acid (each at 100, 150 and 200 ppm) along with sucrose 5% in all the above holding solutions and control. The water, quality and vase life parameters were observed in both the cultivars. Holding of carnation flowers with citric acid 150 ppm + sucrose 5% resulted in maximum CUW (25.30 and 24.19g flower-1), and minimum CTLW (19.80 and 20.74g flower-1 respectively), and STS 1.0 mM + Sucrose 5% resulted in maximum fresh weight (15.56 and 14.64g flower-1), diameter of the flower (7.85 cm and 7.53 cm), slowest stem strength (88.47° and 87.66°), with vase life of (7.76 and 7.34 days) as compared with (5.72 and 4.96 days) in control in both the cultivars. Among different chemicals STS 1.0 mM + Sucrose 5% was found highly effective for longevity of carnation flowers.